Knockdown lncRNA DLEU1 Inhibits Gliomas Progression and Promotes Temozolomide Chemosensitivity by Regulating Autophagy - Lv, Qiao-Li; Wang, Li-Chong; Li, Dang-Chi; Lin, Qian-Xia; Shen, Xiao-Li; Liu, Hai-Yun; Li, Min; Ji, Yu-Long; Qin, Chong-Zhen; Chen, Shu-Hui (Frontiers in Pharmacology, 2020)
Gliomas are the most fatal malignant cerebral tumors. Temozolomide (TMZ), as the primary chemotherapy drug, has been widely used in clinic. However, resistance of TMZ still remained to be poor defined. LncRNAs have been reported to play crucial role in progression of various cancers and resistance of multiple drugs. However, the biological function and underlying mechanisms of most lncRNAs in glioma still remain unclear. Based on the TCGA database, a total of 94 differentially expressed lncRNAs, including 16 upregulated genes and 78 downregulated genes were identified between gliomas and normal brain tissues. Subsequently, lncRNA DLEU1, HOTAIR and LOC00132111 were tested to be significantly related to overall survival (OS) between high- and low-expression groups. Additionally, we verified that lncRNA DLUE1 was high expressed in 108 gliomas, compared with 19 normal brain tissues. And high expression of lncRNA DLEU1 predicted a poor prognosis (HR=1.703, 95%CI: 1.133-2.917, p-value=0.0159). Moreover, functional assays revealed that knockdown of lncRNA DLEU1 could suppress the proliferation by inducing cell cycle arrest at G1 phase and reducing the S phase by down-regulating the CyclinD1 and p-AKT, as well as migration and invasion by inhibiting the epithelial-mesenchymal transition (EMT) markers, such as ZEB1, N-cadherin, β-catenin and snail in glioma cells. Furthermore, silencing of lncRNA DLEU1 suppressed TMZ-activated autophagy via regulating the expression of P62 and LC3 and promoted sensitivity of glioma cells to TMZ by triggering apoptosis. Conclusively, our study indicated that lncRNA DLEU1 might performed as a prognostic biomarker and underlying therapeutic target for sensitivity of glioma to TMZ.